2011
DOI: 10.1292/jvms.11-0046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Escherichia coli Isolates from Wild Mice in a Forest of a Natural Park in Hokkaido, Japan

Abstract: ABSTRACT. To reveal the antimicrobial susceptibilities of Escherichia coli isolates from wild mice, 81 E. coli isolates were obtained from 109 voles (Clethrionomys spp.), 52 large Japanese field mice (Apodemus speciosus) and 19 small Japanese field mice (A. argenteus) captured in a forest of a natural park in Hokkaido, Japan. Seventy-eight of the 81 E. coli isolates were susceptible to all 10 antimicrobial agents tested. One E. coli isolate was resistant to ampicillin, dihydrostreptomycin, kanamycin, chloramph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Escherichia coli is a commensal bacterium prevalent in the intestines of many animal species and is used as a bacterial indicator of AMR [8]. Recent studies on antimicrobial-resistant bacteria in wild animals in Japan revealed a low prevalence of antimicrobial-resistant E. coli in Japanese serows in the 1980s [15], wild mice in 2006 [11], wild cranes in 2007-2008 [16], deer and wild boars in 2013-2017 [1], deer in 2016-2019 [27], great cormorants in 2018-2019 [20], greater white0-fronted geese in 2019 [7], and Amami rabbits in 2017-2020 [18]. However, the application of antimicrobial-containing media for the isolation of antimicrobial-resistant E. coli indicated a high prevalence of fluoroquinoloneresistant E. coli in deer in urban regions [10] and extended-spectrum beta-lactamase (ESBL)-producing E. coli in weasels around animal facilities [33].…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is a commensal bacterium prevalent in the intestines of many animal species and is used as a bacterial indicator of AMR [8]. Recent studies on antimicrobial-resistant bacteria in wild animals in Japan revealed a low prevalence of antimicrobial-resistant E. coli in Japanese serows in the 1980s [15], wild mice in 2006 [11], wild cranes in 2007-2008 [16], deer and wild boars in 2013-2017 [1], deer in 2016-2019 [27], great cormorants in 2018-2019 [20], greater white0-fronted geese in 2019 [7], and Amami rabbits in 2017-2020 [18]. However, the application of antimicrobial-containing media for the isolation of antimicrobial-resistant E. coli indicated a high prevalence of fluoroquinoloneresistant E. coli in deer in urban regions [10] and extended-spectrum beta-lactamase (ESBL)-producing E. coli in weasels around animal facilities [33].…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is used as one of the representative species for the national surveillance of antimicrobial-resistant bacteria in farm animals [ 13 ], and antimicrobial-resistant E. coli has been found in various wild animals [ 7 , 26 ]. In Japan, antimicrobial-resistant E. coli strains have been derived from wild mouse, boar, and sika deer [ 3 , 12 ]. However, the survey areas used in previous studies were limited, and nationwide surveillance is required.…”
mentioning
confidence: 99%
“…In addition, only one isolate from deer exhibited resistance to CIP. Regarding the resistance to β-lactam antibiotics in wild animals in Japan, penicillin antibiotics were tested before 2000 [12,13,20,26], whereas, from then on, both penicillin and cephalosporin antibiotics were tested [11,22]. Resistance to penicillin antibiotics was rarely found, and resistance to cephalosporins was never detected, except for E. coli resistance to cephalothin in 6.5% of Japanese monkeys from the Shimokita Peninsula of Aomori Prefecture [22].…”
mentioning
confidence: 99%